Pyrrolo[2,3-d]pyrimidine (7-deazapurine) as a privileged scaffold in design of antitumor and antiviral nucleosides - Perlíková, Pavla; Hocek, Michal (Medicinal research reviews, 2017)
7-Deazapurine (pyrrolo[2,3-d]pyrimidine) nucleosides are important analogues of biogenic purine nucleosides with diverse biological activities. Replacement of the N7 atom with a carbon atom makes the five-membered ring more electron rich and brings a possibility of attaching additional substituents at the C7 position. This often leads to derivatives with increased base-pairing in DNA or RNA or better binding to enzymes. Several types of 7-deazapurine nucleosides with potent cytostatic or cytotoxic effects have been identified. The most promising are 7-hetaryl-7-deazaadenosines, which are activated in cancer cells by phosphorylation and get incorporated both to RNA (causing inhibition of proteosynthesis) and to DNA (causing DNA damage). Mechanism of action of other types of cytostatic nucleosides, 6-hetaryl-7-deazapurine and thieno-fused deazapurine ribonucleosides, is not yet known. Many 7-deazaadenosine derivatives are potent inhibitors of adenosine kinases. Many types of sugar-modified derivatives of 7-deazapurine nucleosides are also strong antivirals. Most important are 2'-C-methylribo- or 2'-C-methyl-2'-fluororibonucleosides with anti-HCV activities (several compounds underwent clinical trials). Some underexplored areas of potential interest are also outlined.
Keywords: Animals; Antiviral Agents; HeLa Cells; Hep G2 Cells; buňky Hep G2; antivirové látky; screeningové testy protinádorových léčiv; puriny; Nucleosides; lidé; HeLa buňky; Antineoplastic Agents; protinádorové látky; A549 Cells; nukleosidy; racionální návrh léčiv; Purines; Drug Design; Drug Screening Assays, Antitumor; zvířata; buňky A549; Humans